METASTASIS OF SUBMANDIBULAR ADENOID CYSTIC CARCINOMA TO THE FEMUR BONE CAUSING PATHOLOGICAL FRACTURE: A CASE REPORT - Karaca, Mustafa Onur; Balaban, Kamil; Yıldız, Hüseyin Yusuf (Sanamed, 2022)
Introduction: Adenoid cystic carcinoma (ACC) is a rare head and neck malignancy and is likely to be diagnosed in the major salivary glands. It's also known for its slow clinical course and prolonged survival unless no distant metastasis occurs. Even after a long period from the detection of the primary tumor, metastasis to the lung, brain, liver, and bone has a tendency to occur.Case presentation: We report a 53-year-old man who presented with a pathological femur fracture thirteen years after the presentation of submandibular ACC. Our patient reported an improved patient-reported outcome after undergoing resection hemiarthroplasty for his bone metastasis. Conclusion: We tried to accentuate the importance of periodical visits for the probability of distant metastasis and the work-up if it's necessary in such a rare case. It should be kept in mind that proper management of bone metastasis may lead to improvements in the quality of life.
Keywords: Adenoid cystic carcinoma; submandibular gland; bone metastasis; pathological fracture; femur